PELATIHAN PENGAJARAN LITERASI BAHASA INGGRIS UNTUK UTBK DI KALANGAN GURU BAHASA INGGRIS DI SMAS HARAPAN 3 DELITUA - Yunanda, Fachri; Asrul, Nurmahyuni; Husda, Azizah (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2025)
The purpose of this community service is to enhance English language teachers' skills through English Literacy instruction training for the computer-Based Written Examination (UTBK). This activity responds to the need to improve English language teaching quality, particularly in English Literacy in schools. English teachers from SMAS Harapan 3 Deli Lama participated in the training. The program consists of theoretical and practical sessions aimed at enhancing participants' understanding of English Literacy teaching strategies and structures. Additionally, it seeks to improve their overall English proficiency. English pre- and post-tests, along with participant satisfaction questionnaires, were used for evaluation. Evaluation results show that teachers achieved higher English scores post-training. Participants also reported increased confidence, improved English literacy teaching skills, and appreciation for relevant and beneficial training materials.